Histological conversion from adenocarcinoma to small cell carcinoma of the lung after treatment with an immune checkpoint inhibitor: a case report. Issue 4 (23rd May 2020) - Miura, Naoko; Matsubara, Taichi; Takamori, Shinkichi; Haratake, Naoki; Toyozawa, Ryo; Yamaguchi, Masafumi; Seto, Takashi; Taguchi, Kenichi; Takenoyama, Mitsuhiro
Abstract: The transformation of adenocarcinoma to small cell lung cancer has been reported as acquisition of resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors. We here report a patient who presented histologically confirmed transformation of adenocarcinoma to small cell lung cancer after treatment with immune checkpoint inhibitor. A 65-year-old man was treated with pembrolizumab as first-line therapy and achieved temporarily a stable disease with progression after six cycles of this agent. At that stage, a transbronchial biopsy showed small cell lung cancer, and he was found to have high serum concentrations of neuron-specific enolase despite concentrations of numerous tumor markers, including neuron-specific enolase, having been within normal limits at the time of presentation. The patient thereafter was treated as a small cell carcinoma patient using cisplatin plus irinotecan and amrubicin.